Integration of Phase-Change Materials with Electrospun Fibers for Promoting Neurite Outgrowth under Controlled Release - Xue, Jiajia (Adv Funct Mater, 2018)
We report a temperature-regulated system for the controlled release of nerve growth factor (NGF) to promote neurite outgrowth. The system is based upon microparticles fabricated using coaxial electrospray, with the outer solution containing a phase-change material (PCM) and the inner solution encompassing payload(s). When the temperature is kept below the melting point of the PCM, there is no release due to the extremely slow diffusion through a solid matrix. Upon increasing the temperature to slightly pass the melting point, the encapsulated payload(s) can be readily released from the melted PCM. By leveraging the reversibility of the phase transition, the payload(s) can be released in a pulsatile mode through on/off heating cycles. The controlled release system is evaluated for potential use in neural tissue engineering by sandwiching the microparticles, co-loaded with NGF and a near-infrared dye, between two layers of electrospun fibers to form a tri-layer construct. Upon photothermal heating with a near-infrared laser, the NGF is released with well-preserved bioactivity to promote neurite outgrowth. By choosing different combinations of PCM, biological effector, and scaffolding material, this controlled release system can be applied to a wide variety of biomedical applications.